Caracterización de las alternativas ecoturísticas del cantón Saquisilí. - Guamani Oña, Jessica Liseth (2020)
This research project characterized the existing ecotourism alternatives at Saquisilí Canton, for its development 3 specific objectives were proposed. In the first objective, tourism system was analyzed through a bibliographic review from: books, web pages, articles or thesis related to the problem under revision, in addition surveys were applied to tourists in the Canton, interviews with involved people in area from Local Gad, such as Parish Gads, and tourism servers involved in canton development. In the second objective, natural and cultural attractions were invented using the “Methodology for the Hierarchy of Attractions and Tourist Spaces Generation in Ecuador” created by the Ministry of Tourism, a methodology that allowed to identify 5 tourist attractions in Saquisilí parish, 7 tourist attractions in Canchagua parish; 1 tourist attraction in Chantilin parish and 5 tourist attractions in Cochapamba parish; obtaining a total of 18 tourist attractions in 4 parishes of Saquisili Canton. Finally, for the fulfillment of the third objective, 2 maps were designed using TICs (GPS, ArcGIS) that contain the location of the canton, access roads, rivers, parish headwaters, attractions and ecotourism alternatives.